2020
DOI: 10.1155/2020/8872438
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Influence of Water Content on the Mechanical Properties of Coal under Conventional Triaxial Compression

Abstract: The presence of water is one of the most important factors in coal mining, and it has a dual influence on the mechanical behavior of rock. To study the influence of water content on the mechanical properties of coal under complicated stress conditions, dry coal specimens and wet coal specimens with water contents of 1.8% and 3.6% were conducted by uniaxial and conventional triaxial compression tests. The relations between the uniaxial compressive strength, deformation, and water content were observed. The redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Qin et al [19] investigated the impact of water on the mechanical properties and acoustic emission characteristics of raw coal samples by loading experiments, and they discovered that as moisture content increased, the uniaxial compressive strength of the coal samples and the cumulative ring count of acoustic emission gradually decreased. Feng et al [20], Yao et al [21], Zhang et al [22], and Liu et al [23] also obtained similar experimental results: the uniaxial compressive strength and Young's modulus of coal samples decline monotonically as moisture content rises. Wang et al [24], Wang et al [25], and Zhu et al [26] performed uniaxial compression experiments on briquette coal samples varying in moisture content and found that with increasing moisture content, the mechanical strength indexes such as uniaxial compressive strength (UCS) and Young's modulus first increased and then decreased, which were different from the experimental phenomena of raw coal samples [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Qin et al [19] investigated the impact of water on the mechanical properties and acoustic emission characteristics of raw coal samples by loading experiments, and they discovered that as moisture content increased, the uniaxial compressive strength of the coal samples and the cumulative ring count of acoustic emission gradually decreased. Feng et al [20], Yao et al [21], Zhang et al [22], and Liu et al [23] also obtained similar experimental results: the uniaxial compressive strength and Young's modulus of coal samples decline monotonically as moisture content rises. Wang et al [24], Wang et al [25], and Zhu et al [26] performed uniaxial compression experiments on briquette coal samples varying in moisture content and found that with increasing moisture content, the mechanical strength indexes such as uniaxial compressive strength (UCS) and Young's modulus first increased and then decreased, which were different from the experimental phenomena of raw coal samples [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 66%
“…Feng et al [20], Yao et al [21], Zhang et al [22], and Liu et al [23] also obtained similar experimental results: the uniaxial compressive strength and Young's modulus of coal samples decline monotonically as moisture content rises. Wang et al [24], Wang et al [25], and Zhu et al [26] performed uniaxial compression experiments on briquette coal samples varying in moisture content and found that with increasing moisture content, the mechanical strength indexes such as uniaxial compressive strength (UCS) and Young's modulus first increased and then decreased, which were different from the experimental phenomena of raw coal samples [19][20][21][22][23]. There was no systematic study of the difference between the two experimental phenomena.…”
Section: Introductionmentioning
confidence: 66%
“…Currently, experimental investigations on waterproof coal pillars primarily focus on the weakening effects of water content on the mechanical parameters of coal samples (Yao et al 2021b). Yao et al (2020) conducted tests involving variable-angle shear on coal samples with different water contents, while (Lu et al 2016;Wang et al 2018;Zhang and Nie 2020) performed uniaxial and triaxial tests on coal samples with varying water contents. The findings from these studies consistently demonstrate that the mechanical properties of coal pillars, such as compressive strength, shear strength, friction angle, and cohesion, decrease with an increase in water content.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a comprehensive understanding of the mechanical response and failure characteristics of coal and rock under water-bearing conditions is highly important for ensuring safe production and disaster warning in coal mines.In recent decades, many mechanical tests have been conducted on coal and rock under different water content conditions 22 , and fruitful results have been achieved. Destructive loading methods include uniaxial compression 23,24 , triaxial compression 25,26 , Brazilian splitting 27,28 , four-point bending 29 , and notched semicircular bending (NSCB) 30,31 of water-bearing coal and rock. In general, as the moisture content increases, the strength,…”
mentioning
confidence: 99%
“…In recent decades, many mechanical tests have been conducted on coal and rock under different water content conditions 22 , and fruitful results have been achieved. Destructive loading methods include uniaxial compression 23,24 , triaxial compression 25,26 , Brazilian splitting 27,28 , four-point bending 29 , and notched semicircular bending (NSCB) 30,31 of water-bearing coal and rock. In general, as the moisture content increases, the strength,…”
mentioning
confidence: 99%